Exploring the genetic diversity and population structure of Ailanthus altissima using chloroplast and nuclear microsatellite DNA markers across its native range - Saina, Josphat K.; Li, Zhi-Zhong; Ngarega, Boniface K.; Gituru, Robert W.; Chen, Jin-Ming; Liao, Yi-Ying (Frontiers in Plant Science, 2023)
Understanding how anthropogenic disturbance affects the genetics of tree species is essential, however, how the tree populations in the wild can tolerate these anthropogenic activities remains unexplored. Considering the ongoing and intensifying anthropogenic disturbances, we used Ailanthus altissima to gain new insight into the effects of these pressures on genetic variability in natural and disturbed forests. The genetic diversity and population structure of A. altissima was analyzed by nuclear and chloroplast microsatellite markers. The genetic diversity across the 34 study populations based on EST-SSRs was moderate to high (HE= 0.547-0.772) with a mean HE of 0.680. Bayesian clustering, principal coordinate analysis (PCOA), and discriminant analysis of principal component (DAPC) congruently divided the populations into three distinct groups based on EST-SSRs. Allelic combinations of 92 different chloroplast size variants from 10 cpSSR loci resulted in a total of 292 chloroplast haplotypes. The mean haplotypic diversity was relatively high (HE= 0.941), and the mean haplotypic richness was 2.690, averaged across the 34 populations of A. altissima. Values of FST in A. altissima from chloroplast and nuclear markers were 0.509 and 0.126 respectively. Modeling results showed evidence for population range contraction during the Last Glacial Maximum with subsequent population expansion in the Holocene and the Future. Although genetic variation did not differ substantially across disturbed and undisturbed sites, there were small trends indicating higher genetic diversity and population bottlenecks in disturbed forests. As a result, disrupted ecosystems might display surprising genetic patterns that are difficult to predict and should not be overlooked.